Sheltered Math for Emergent Bilinguals: A Case Study of a Novice High School Teacher - Tigert, Johanna M.; Fotouhi, Golnar (John Wiley & Sons, 2025)
Sheltered English Immersion (SEI) is a common instructional approach to serve Emergent Bilingual (EB) students through Content-Based Instruction. However, little is known about how novice teachers implement SEI in their content areas once they enter the profession. This dearth of research is particularly pronounced in math, a content area where research has shown teachers to be prone to neglect the language learning needs of EBs. In this case study, we examine the perceptions of and the implementation of SEI by a novice mathematics teacher who had completed a single SEI course during her teacher education program. The findings showed that the teacher implemented some SEI strategies well, such as teaching vocabulary and modifying her instructional materials with visuals, color-coding, and guided notes. However, she struggled to chunk information for her students and did not engage them in extended mathematical discourse or promote translanguaging in home languages. The study shows that a single SEI course does not provide sufficient tools for a novice teacher to fully meet the needs of EBs. Implications for teacher education and research are discussed.